Some Structural Features and Feeding Characteristics of Dairy Cattle Enterprises in Kastamonu Province - Ayan, Özlem; Tüzemen, Naci (Mehmet Akif Ersoy Universitesi Fen Bilimleri Enstitusu Dergisi, 2025)
This study examines the structural features and producer characteristics of dairy cattle farms in Kastamonu province and its districts. Data were collected through surveys using a random sampling method. The study shows that most farms are small-scale family operations withoutexternal labor, and all are members of at least one agricultural union. Approximately 77.2% offarms produce their own roughage, while silage is the least used feed due to limited irrigation,small land areas, financial constraints, wild boar pressure, and lack of knowledge on silagepreparation. Cattle are generally fed twice daily in barns, and in suitable areas, 83% of farms usepasture grazing. In the past decade, the number of farms has grown to supplement householdincome. While barns are adequately sized, bedding is not used due to financial limitations.Equipment such as automatic waterers, feed crushers, and mixers are commonly utilized, with 68%of farms using milking machines. Dairy products are sold through cooperatives and local markets orused for household consumption. Veterinary services are mainly provided by ProvincialDirectorates of Agriculture, with private veterinarians handling artificial insemination and majorhealth issues. Farmers expect government support in low-interest loans, veterinary care, training,incentives, and grants.